Zgodność z rzeczywistością. Uwagi o Jacka J. Jadackiego teorii prawdy - Witek, Maciej (Filozofia Nauki, 2005)
The author starts with the assumption that a popular idea, according to which a true sentence corresponds with reality, is adequate. Therefore, any adequate theory of truth has to account for it. It turns out, however, that it is the epistemic conception, not the correspondence one, that meets such a demand. In order to justify his claim, the author discusses Jacek J. Jadacki's theory of truth. Roughly speaking, the theory in question states that if a given sentence refers to a certain state of affairs - that function a the sentence's semantic value - then the sentence is true if and only if the relevant state of affairs holds. In short, the theory defines the truth of a given sentence in terms of the holding of the state of affairs to which the sentence refers. It remains to be explained, therefore, what it is, for a given state of affairs to hold. The author considers three possible accounts of the holding of the state of affairs. According to the first one, the sentence's semantic value is either a mental representation or an ideal entity grasped in the subjective episode of understanding. Such a mental or ideal state of affairs holds if it has its real counterpart. The second ac-count is based on the idea that real states of affairs constitutes a subclass of all describeable states of affairs. A given state of affairs holds if and only if it belongs to this special class. According to the third interpretation, a holding state of affairs is the semantic value of a true sentence. The author argues that the first account gives rise to the suspect question on the nature of either the relation of mental representation or the relation of exemplification. The second account, in turn, seems to require a controversial assumption that existence is a property. Taking into account those and similar problems, we have no alternative but to embrace the third option, according to which a given state of affairs holds because it is the semantic value of a true sentence. The truth of a sentence, in turn, has to be conceived as its rational acceptability.